Analisis Kekebalan Hukum Bagi Komite Stabilitas Sistem Keuangan (KSSK) Berdasarkan Undang-Undang Republik Indonesia Nomor 2 Tahun 2020 Tentang Penetapan Peraturan Pemerintah Pengganti Undang-Undang Nomor 1 Tahun 2020 Tentang Kebijakan Keuangan Negara Dan Stabilitas Sistem Keuangan Untuk Penanganan Pandemi Corona Virus Disease 2019 (Covid- 19) Dan/Atau Dalam Rangka Menghadapi Ancaman Yang Membahayakan Perekonomian Nasional Dan/Atau Stabilitas Sistem Keuangan Menjadi Undang-Undang - Gunawan, Siti Rachmawati (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2020)
To overcome the worst economic crisis caused by the Corona Virus Disease - 19 pandemics, the Government issued Perppu No.1 of 2020 which regulates the incorporation of the Financial System Stability Committee (KSSK). Whereas in the Perppu number 1 of 2020, it is stipulated that the KSSK cannot be sued or prosecuted criminally, and the decisions made by the KSSK are also not subject to the State Administrative Court. Which such regulation creates absolute legal immunity for KSSK.